2021
DOI: 10.1051/e3sconf/202123204007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Awareness and Perception of Climate Change between Proklim and Non-Proklim Farmers in Sleman District

Abstract: Program kampung iklim (Proklim) was launched by the Government to increase the implementation of the climate change adaptation strategy. The decision to adopt an adaptation strategy is influenced by farmers’ perceptions of climate change. This study aims to determine the level and compare the awareness of the climate change and perceptions of the climate change risks, among farmers from the Proklim and non-Proklim locations. The study was conducted in 3 sub-districts that have Proklim location, in Sleman Regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This finding is in line with the findings of previous studies, stating that the majority of farmers perceive the occurrence of climate change, marked by an increasingly hot temperature and declined rainfall [ 16 , 20 , 45 – 49 ]. In addition, farmers who have experienced crop failure due to climate change such as drought or flooding will be more aware about climate change [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the findings of previous studies, stating that the majority of farmers perceive the occurrence of climate change, marked by an increasingly hot temperature and declined rainfall [ 16 , 20 , 45 – 49 ]. In addition, farmers who have experienced crop failure due to climate change such as drought or flooding will be more aware about climate change [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Implementing effective communication techniques and policy interventions can enhance the influence of awareness and perception on the direction of financial resources towards sustainable projects [26]. Research has shown that effectively planned climate change communication campaigns [27] and government policies (e.g., subsidies for renewable energy) can increase public knowledge and understanding, leading to increased expenditures in sustainable projects [28].…”
Section: Literature Reviewmentioning
confidence: 99%